The Estimation of Final Consumption Expenditures - Vltavská, Kristýna; Sixta, Jaroslav (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
17-th AMSE. Applications of Mathematics in Economics. International Scientific Conference: Poland, 27-31 Agust, 2014. Conference Proceedings Full Text Papers. The International Scientific Conferences "Applications of Mathematics and Statistics in Economics" are organized each year by three Departments of three Universities from three countries - University of Economics, Prague (Czech Republic), Matej Bel University in Banská Bystrica (Slovakia) and Wrocław University of Economics (Poland)
Keywords: consumption of households; expenditures; ESA 1995